Langya virus outbreak: current challenges and lesson learned from previous henipavirus outbreaks in China, Australia, and Southeast Asia - Ridwan Olamilekan Adesola; Adriana Viola Miranda; Yeuk Shun Joshua Tran; Ibrahim Idris; Xu Lin; M. B. N. Kouwenhoven; Don Eliseo Lucero-Prisno (Bulletin of the National Research Centre, 2023)
Abstract Background and aims A new novel virus, Langya virus (LayV), was detected in China in August 2022, 3 years after the COVID-19 pandemic. LayV is similar to the previously discovered Mojiang henipavirus. Other zoonotic henipaviruses include the Hendra and Nipah viruses. The emergence of the zoonotic Langya virus is attributed to climate change and wildlife encroachment, as LayV is detected in shrews. Those who are infected in China showed various symptoms, but no deaths have been recorded yet. This review aims to shed light on the current state of Langya virus outbreak, its infection control efforts, and the remaining challenges that need to be addressed to curb the outbreak. Methods We utilized online publication databases such as PubMed, Google Scholar, and Scopus in writing this review article. Results A surveillance study on thirty-five febrile patients in Eastern China identified the Langya virus outbreak. The current efforts from the Chinese government and health authorities to reduce the transmission and spread of Langya virus such as isolation and characterization of LayV, challenges associated with the increase in cases of LayV, and trackable recommendations such as strengthening the healthcare system in China, sensitization of people about risks associated with Langya virus outbreaks, creating an intensive surveillance system network, etc. were discussed. Conclusion It is germane and pertinent that the Chinese government and health authorities continue to intensify efforts against Langya virus and address the challenges to effectively reduce transmission.